Alterations of glycaemia, insulin resistance and body mass index within the C-peptide optimal range in non-diabetic patients - Kron, Vladimír; Verner, Miroslav; Smetana, Pavel; Janoutová, Jana; Janout, Vladimír; Martiník, Karel (Journal of Applied Biomedicine, 2020)
The study focused on changes or cut-offs of glycaemia, insulin resistance and body mass index within the C-peptide reference range (260-1730 pmol/l). The metabolic profile of individuals in the Czech Republic without diabetes (n = 3186) was classified by whiskers and quartiles of C-peptide into four groups with the following ranges: 290-510 (n = 694), 511-710 (n = 780), 711-950 (n = 720) and 951-1560 pmol/l (n = 673). Fasting levels of glucose, insulin, HOMA IR (Homeostasis Model Assessment for Insulin Resistance) and BMI (body mass index) were compared by a relevant C-peptide range. Participants taking medication to control glycaemia were excluded. The evaluation involved correlations between C-peptides and the above parameters, F-test and t-test. Changes in glucose levels (from 5.3 to 5.6 mmol/l) between the groups were lower in comparison to insulin, which reached relatively greater changes (from 4.0 to 14.2 mIU/l). HOMA IR increased considerably with growing C-peptide concentrations (0.9, 1.5, 2.2 and 3.5) and BMI values showed a similar trend (28.3, 31.0, 33.6 and 37.4). Considerable changes were observed for insulin (5.2 mIU/l, 57.8%) and HOMA IR (1.3, 61.3%) between groups with C-peptide ranges of 711-950 and 951-1560 pmol/l. Although correlations involving C-peptide, insulin, glucose and BMI seemed to be non-significant (up to rxy = 0.25), the mean values of insulin, HOMA IR and BMI showed statistically significant changes between all groups with various C-peptide concentrations (p ≤ 0.001). Generally, most important differences appeared in glucose metabolism and body mass index between C-peptide ranges of 711-950 and 951-1560 pmol/l. Absolute and relative changes of C-peptide concentrations are possible to use for the assessment of glucose regulatory mechanism. The spectrum of investigated parameters could be a useful tool to prevent the risks linked with the alterations of glycaemia.
Keywords: senioři; index tělesné hmotnosti; bazální metabolismus; statistika jako téma; C-Peptide; glukózový toleranční test; krevní glukóza; mladiství; Statistics as Topic; Middle Aged; Adult; mladý dospělý; inzulin lidský; Body Mass Index; Blood Glucose; Young Adult; Humans; Insulin, Regular, Human; lidé středního věku; C-peptid; dospělí; inzulinová rezistence; Insulin Resistance; Aged; Glucose Tolerance Test; Adolescent; lidé; Basal Metabolism